Morphophysiologic changes of soybean in flooded soils - Pires, João Leonardo Fernandes; Soprano, Eliséo; Cassol, Bibiana (Pesquisa Agropecuaria Brasileira, 2002)
There are restrictions to the growth of plants in flooded soils, and this limits their agricultural exploration to few species. Soybean is becoming an alternative, due to its high adaptation capacity to these conditions. The objective of this work was to identify the forms of adaptation of soybean in flooded soils, and to establish the best strategy for supplying N in flooded conditions. An experiment was carried out in greenhouse in the Faculdade de Agronomia of Universidade Federal do Rio Grande do Sul (UFRGS), in Brazil, from September to November 1998. Two cultivars of soybean (FT-Abyara and BR 4) grown under two humidity conditions (flooded soil and field capacity) and two strategies for supplying nitrogen (inoculation and mineral N) were tested. The soybean stayed under flood from stadium V2 to V5 (21 days). Soybean presented mechanisms (stem base hypertrophy and adventitious roots with aerenchyma), that allowed its adaptation to hypoxia conditions under flooded soil. There was reduction in the levels of N, K, Mg and Mn and increase in the level of Fe in the leaves when flooded. Differences existed between cultivars under flooded soil; cultivar FT-Abyara was the best adapted. Stem diameter under flooded conditions was the most important characteristic in the differentiation of cultivars for tolerance to flooding. The best strategy for supplying N in conditions of flooded soil was the application of mineral N in covering. Even under flood, nodulation in soybean happened.